Hydraulic regulation and control of photosynthesis in Pinus ponderosa - Hubbard, Robert M., author; Binkley, Dan, advisor; Ryan, Michael G., advisor (Colorado State University. Libraries, 2000)
Foresters and ecologists have long recognized that all trees eventually stop growing significantly taller, and all forests decline in net primary productivity after canopy closure. The hydraulic limitation hypothesis suggests that these patterns can be explained by the fact that as trees grow larger and older, whole tree leaf specific hydraulic conductance (KL) declines. If stomatal control acts to maintain constant leaf water status, lower KL will cause lower stomatal conductance and photosynthesis, reducing carbon gain in old, tall trees. I performed field and laboratory studies to test several physiological aspects of this hypothesis and to examine how hydraulics affect stomatal behavior and leaf gas exchange in ponderosa pine. My specific hypotheses were: 1) KL is lower in tall (~33m and 230 yrs old) compared to short (~10m and 45yrs old) ponderosa pine trees causing decreased stomatal conductance (g5) and photosynthesis (A) throughout the day; 2) reducing or increasing KL in trees or branches will cause a proportional change in stomatal conductance and photosynthesis and 3) longer path lengths cause KL to be lower at the tops versus the bottom of open grown, old tree crowns. Our study site was an open grown stand of ponderosa pine growing on the east side of the Oregon Cascades. In testing hypothesis 1, I found that KL at the end of the summer of 1995 (calculated from leaf water potential and leaf gas exchange measurements on one-year old needles) was 44% lower in old compared to young trees. Whole-tree sap flux per unit leaf area averaged 53% lower in old compared to young trees. In old trees, stomatal conductance (g5) and assimilation (A) exhibited a steeper decline with air saturation deficit (D) for the entire summer. Mean values for g5 and A were approximately 32% and 21% lower respectively for old and young trees at typical midday D values (2.5-3.0 kPa). Removal of 50% of the foliage from a set of experimental branches on old trees caused g5 and A to decline less steeply with D in early summer, but values were not significantly different from controls in late summer. Cutting transverse notches in branches on young trees had no effect on the response of g5 and A with D. Leaf nitrogen content and photosynthetic capacity were identical suggesting differences in g5 and A between old and young trees were not caused by differences in photosynthetic capacity. These results suggest that lower KL limits stomatal conductance and photosynthesis in tall, old open grown ponderosa pine at our site. If stomatal control acts to maintain constant leaf water status during transpiration, and if lower stomatal conductance reduces assimilation, hypothesis two suggests that reducing KL will result in a proportional decline in g5 and assimilation. To vary KL, we systematically reduced stem hydraulic conductivity (k) of well-watered ponderosa pine seedlings (Pinus ponderosa) using air injection to induce cavitation while simultaneously measuring the response of canopy gas exchange in the laboratory under constant light and D. Short-statured seedlings (< 1 m tall) and hour-long equilibration times promoted steady-state flow conditions. We found that g5 transpiration, A, and KL all declined with decreasing k (P < 0.001). This response was independent of bulk leaf water potential which remained constant near -1.5 MPa, except at the extreme 99% reduction in k when it fell to -2.1 MPa. Because stomata closed and bulk leaf water potential (ψleaf) was maintained as KL declined, stomatal conductance and assimilation were directly proportional to KL (R2 > 0.90). These results suggest that stomata in ponderosa pine seedlings exhibit a linear response to changes in KL and that changes in KL affect whole plant carbon gain. To assess the effects of path length within individual tree crowns (hypothesis 3), we measured leaf gas exchange, foliar δ13C, branch sap flux, and KL on branches at two different heights (~ 10 and 25m) within four tall (~ 30m) ponderosa pine. We found no difference in leaf gas exchange, branch sap flux or KL between the upper and lower canopy of our study trees. We also found significantly lower leaf area to sapwood ratios (Al:As) in branches from the upper compared to the lower canopy (P = 0.03). Al:As averaged 0.17 (m2 cm-2) and 0.27 in the upper and lower canopy respectively. Leaf specific branch conductance did not differ with canopy height (P = 0.24). These results indicate that increases in path length may not cause lower Kl in ponderosa pine at our site because ponderosa pine may mitigate the effects of increased path length by changing the ratio of transpirational to transport tissues. In general, data from this dissertation support the hydraulic limitation hypothesis. Lower KL in old compared to young ponderosa was associated with lower g5 and A, and there is convincing evidence from the laboratory study that ponderosa pine stomata regulate to maintain a constant leaf water potential and that the relationship between g5 with KL is linear. Although changes in the ratio of leaf area to sapwood area may mitigate the effects of increased path length in single ponderosa pine, there is good evidence that lower KL causes lower g5 and A in old compared to young ponderosa at our site (this study and Ryan et al. 2000). Explaining these differences will require future research to focus on how other hydraulic properties such as sapwood permeability, increased branch length and, or larger number of branch junctions change with tree age and size.
Keywords: ecology; botany